Simulation and Comparison Between Slow and Fast FH/BPSK Spread Spectrum Using Matlab (Journal of University of Babylon for Engineering Sciences, 2018)
This paper investigates the properties and applications of Frequency Hopping Spread Spectrum (FHSS).  FHSS is radio communication technique by which the sender of information sends the data on a radio channel, which changes the frequency of transmission based on a predetermined sequence of code. The FHSS has many advantages over traditional modulation methods, it can overcome fading, multipath channels and interferences. Hence the interception becomes difficult. This security feature makes FHSS more preferable for  military applications. At the receiver side, the signal is demodulated by the same carrier signal for which frequency changes by the same code sequences used by the sender. This paper presents two types of FHSS, slow and fast. The  simulation procedures of both types were  implemented and applied on   Frequency Hopping /Binary Phase Shift Keying (FH/BPSK) spread spectrum system using MATLAB. The simulation sequences for fast and slow frequency hopping is the same in number  and frequencies of spreading carriers and both used BPSK traditional modulation type. The  comparison  results  based on their power spectral density   show that the fast frequency hopping is more resistive to noise the slow one.